IMPLEMENTATION OF DERADICALIZATION POLICIES TO PREVENT TERRORIST ACTS IN EAST JAVA - Arinto, Singgih Pambudi; Hakim, Abdul; Sarwono, Sarwono; Hermawan, Romy (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This study examines the implementation of deradicalization policies with the aim of obtaining a comprehensive understanding of (1) the process of implementing deradicalization policies, (2) the actors involved or playing a role in the implementation of these policies, and (3) the impacts of implementing deradicalization policies. To achieve these objectives, we collected data through in-depth interviews, observations, and secondary data documentation. The data were analyzed using the Interactive Model. Based on the data analysis and discussion, the conclusions are as follows. First, the success of the policy implementation process is determined by: (a) the clarity and detail of the policy content, including the tasks of the implementers; (b) the implementation strategies used by the policy implementers; and (c) support from the environment in which the policy is implemented. Second, the effectiveness of the actor’s roles in the policy implementation process will be better if (a) there is communication, coordination, and facilitation of the actors’ needs in carrying out their tasks; (b) cooperation and mutual understanding of each actor’s role are established; and (c) the target groups and the community are involved from the planning stage to the implementation. Third, to achieve direct impacts, practical activities that provide economic benefits and skill development for the target groups are required. For indirect impacts, active involvement of the target groups and the community is necessary to collectively build awareness for improved attitudes and behaviors.